2020
DOI: 10.3389/fmicb.2020.556118
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Mixing Kentucky Bluegrass With Red Fescue via Plant-Soil Interactions in Black Soil of Northeast China

Abstract: Continuous monoculture of cool-season turfgrass causes soil degradation, and visual turf quality decline is a major concern in black soil regions of Northeast China. Turf mixtures can enhance turfgrass resistance to biotic and abiotic stresses and increase soil microbial diversity. Understanding mechanism by plant-soil interactions and changes of black soil microbial communities in turf mixture is beneficial to restoring the degradation of urbanized black soils and maintaining sustainable development of urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…It is in accordance with a previous work which reported that Firmicutes increased by the planting of P. pratensis in a pot experiment [ 38 ]. Moreover, relative abundance of Firmicutes was higher with monoculture of P. pratensis than with the mixture of P. pratensis and Festuca rubra [ 39 ]. This suggested that dominance of P. pratensis in plant community might be favourable for Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…It is in accordance with a previous work which reported that Firmicutes increased by the planting of P. pratensis in a pot experiment [ 38 ]. Moreover, relative abundance of Firmicutes was higher with monoculture of P. pratensis than with the mixture of P. pratensis and Festuca rubra [ 39 ]. This suggested that dominance of P. pratensis in plant community might be favourable for Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are as many combinations of local environmental factors as there are potential customers. Many other benefits of using mixtures have been also described: higher shoot density, enhanced disease and insect resistance, better shade tolerance, earlier spring green-up, better tolerance to low maintenance, and better turf quality [50,[63][64][65][66][67][68][69]. For high-maintenance lawn surfaces such as golf greens or football pitches, in many cases, few, high-quality commercial varieties of one species are mixed [70,71].…”
Section: Lawn Grassesmentioning
confidence: 99%
“…The diversification of cropping systems has been suggested as a way to enhance soil microbiology to promote more sustainable and resilient agricultural systems ( Altieri, 1999 ). Rotation and mixture are being promoted as ecologically sustainable agriculture ( Verret et al, 2020 ; Xie F. C. et al, 2020 ; Xie Y. Y. et al, 2020 ; Jalli et al, 2021 ; Cui et al, 2022 ). It is well known that there are benefits to soil microbial communities and crop productivity in rotation and mixture ( Fujiishi et al, 2020 ; Benitez et al, 2021 ; He et al, 2021 ; Che et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%